Breastfeeding in Bolivia - information and attitudes - Ludvigsson Jonas F (BMC, 2003)
Abstract Background The main objective of the present study was to investigate the relationship between the attitudes of the mother and her family towards breastfeeding and the actual feeding pattern in a Bolivian population. A second objective was to study the relationship between breastfeeding information, specified according to source and timing, and feeding pattern. Methods Cross-sectional interviews with 420-502 Bolivian mothers with an infant less than or equal to 1 year of age. Duration of exclusive breastfeeding, use of prelacteal food and/or colostrum were the main outcome measures. Results The attitudes of the mother, her partner (the infant's father) and the infant's grandmother towards breastfeeding did not influence the infant feeding pattern. Women who had received breastfeeding information from health care personnel before birth or on the maternity ward breastfed exclusively for a longer duration (adjusted p = 0.0233) and avoided prelacteal food to a greater extent (adjusted odds ratio (AOR) = 0.42; 95% confidence interval for adjusted odds ratio (95% CI AOR) = 0.23-0.72). Information from a doctor before birth or on the maternity ward was associated with less use of prelacteal food (AOR = 0.53; 95% CI AOR = 0.31-0.93), an increased use of colostrum (AOR = 3.30; 95% CI AOR = 1.16-9.37), but was not linked to the duration of exclusive breastfeeding (p = 0.1767). Conclusion The current study indicates that breastfeeding information delivered by health care personnel in a non-trial setting may affect the infant feeding pattern including the use of prelacteal foods and colostrum. There was no evidence that the attitudes of the mother, or the infant's father or grandmother influenced actual feeding behavior. The lack of a "negative or neutral attitude" towards breastfeeding in the participants of the current study does, however, diminish the chances to link attitude to feeding behavior.